2022
DOI: 10.3390/land11040474
|View full text |Cite
|
Sign up to set email alerts
|

History of Seoul’s Parks and Green Space Policies: Focusing on Policy Changes in Urban Development

Abstract: Globally, urban areas have been expanding rapidly since industrialization. In South Korea, urban policy has evolved according to urban development, but the change in parks and green spaces policy for a pleasant urban environment is insignificant. The purpose of this study is to present the direction of the Seoul Metropolitan Government’s parks and green spaces policy in terms of green infrastructure, by examining urban policies and changes in the parks and green spaces policy of the Seoul Metropolitan Governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Their study supports the present study's findings that environmental GI has the strongest influence on greenspace perception. This connection can also be supported with public initiatives by local governments in Seoul City to promote urban greenspaces and parks, enhancing recreational opportunities for residents (Choi and Kim, 2022). The study confirms a robust correlation between environmental consciousness and GSP, indicating a stronger connection between residents' environmental sensitivity and their spatial perception of urban nature.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Their study supports the present study's findings that environmental GI has the strongest influence on greenspace perception. This connection can also be supported with public initiatives by local governments in Seoul City to promote urban greenspaces and parks, enhancing recreational opportunities for residents (Choi and Kim, 2022). The study confirms a robust correlation between environmental consciousness and GSP, indicating a stronger connection between residents' environmental sensitivity and their spatial perception of urban nature.…”
Section: Discussionsupporting
confidence: 59%
“…Notably, environmental GI, which indicates individual recognition of biodiversity, ecosystems, and green stewardship, plays a significant role in the GI-GSP relationship. This insight aligns with increasing attention toward urban nature in South Korea's capital region, ranging from individual (Baek et al, 2020) to political efforts by local governments (Choi and Kim, 2022). Baek et al (2020) found that urban residents' desire to engage with nature correlates strongly with their intention to visit greenspaces.…”
Section: Discussionmentioning
confidence: 58%
“…As a result, it would have been di cult to achieve the initially planned sustainability and resilience. Urbanization around the study area has continued since 2003 when the research began; the low-density and low-rise building area was reconstructed into a highdensity and high-rise building area to maximize the pro tability of the highly advantageous location in the new town, as revealed by land cover data and satellite images (4,13).…”
Section: Figure 1 Location Map Of the Study Areamentioning
confidence: 99%
“…Currently, UGS research is clustered around the insights that it brings to relevant policy making [37,38]. Urbanization has led to the evolution of greening policies; however, the two are not yet fully synchronized [39]. Therefore, while some attention has been paid to exploring the relationship between UGS and the associated greening policies in different urbanization stages [20,40], a gap still remains in terms of understanding how different stages of greening policy implementation impact changes in UGS.…”
Section: Introductionmentioning
confidence: 99%